THE ANALYSIS OF TRAINING AND DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT. BANK NEGARA INDONESIA (PERSERO) TBK. MANADO - Rompas, Regina; Saerang, David Paul Elia; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Human resource is very important and considered as a resource that is important to all organizations A company cannot build a good team of working professionals without good human resources. Therefore, solutions is company holds training. The quality of service in a company is reflected from the services provided by its frontliners. When the frontliners successfully apply their training at work, it enables them how to solve the problems. The objectives of this research is to know employee performance after the training and development and the success of the training and development program in PT. Bank Negara Indonesia (Persero) Tbk Manado. This research is a descriptive research. The results of this research by using the In-Depth Interview with all the informants shows that their performance are improved after training, training helps the employees to improve their skill and ability at work, and the success factors of training and development program that really help the employee to understand the material are the good instructor, materials, and facilities. The management of Bank BNI should update its training material, review the time of training, and add more types of training that can help the employees in doing their daily tasks. Â  Keywords: training, development, employee performance Â